Elucidating the role of Cyclooxygenase‐2 in the pathogenesis of oral lichen planus – an immunohistochemical study with supportive histochemical analysis. (27th November 2016) - Singh, Pratyush; Grover, Jasleen; Byatnal, Aditi Amit; Guddattu, Vasudeva; Radhakrishnan, Raghu; Solomon, Monica Charlotte
Abstract : Objective: Oral lichen planus (OLP) is a chronic, inflammatory disorder that affects the oral mucous membrane. During an inflammatory response, several chemokines and cytokines are released by the cells of the immune system. Activation of MMPs, along with mast cell‐derived chymase and tryptase, degrades the basement membrane structural proteins, resulting in basement membrane breaks. Aim: To investigate the association between the COX‐2 expressions, presence of intact or degranulating mast cells within the connective tissue and the extent of basement membrane discontinuity in OLP cases. Methods: This study included a total of 50 formalin‐fixed paraffin‐embedded specimens (FFPE) of histologically confirmed cases of idiopathic oral lichen planus. A retrospective cross‐sectional analysis was carried out by immunohistochemistry to study the epithelial expression of COX‐2 and by the use of special stains such as toluidine blue and periodic acid–Schiff (PAS) to study the mast cell count and basement membrane changes in the oral mucosal tissue, respectively. Results: There was a significant ( P = 0.03) association between the COX‐2 expressions and mast cell count. As the intensity of COX‐2 expression increased from mild to moderate or severe, the number of mast cell count almost doubled. Conclusion: Interaction between upregulation of COX‐2, mast cell and basement membrane sets a vicious cycle which relates to the chronic nature of the disease. Inhibitors of COX‐2 may reduce the inflammatory process preceding the immune dysregulation in OLP.